Voice of the diaspora: An analysis of migrant voting behavior - Jan Fidrmuc; Orla Doyle (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2005)
This paper utilizes a unique dataset on votes cast by Czech and Polish migrants in recent national elections in their home countries. The political preferences of migrants as manifested by their voting behavior are strikingly different from those of their home-country counterparts. In addition, there are important differences in voting patterns across migrants living in different countries. We examine three explanations of migrant voting behavior: adaptive learning; economic self-selection; and political self-selection. Our results suggest that migrant voting behavior is affected by the institutional environment of the host countries, in particular the democratic tradition and the extent of economic freedom. There is little evidence that differences in migrants' political attitudes are caused by pre-migration self-selection with regard to political attitudes, or with regard to economic considerations. The results indicate that the political preferences of migrants change significantly in the wake of migration as migrants adapt to the norms and values prevailing in the host country. This change away from home could be the catalyst of a corresponding change at home.
Keywords: J61; P26; P33; Z13; 330; Voting; election; migration; political resocialization; transition; Wahlverhalten; Tschechisch; Polnisch; Institutionelle Infrastruktur; Polen; Tschechische Republik; Migranten